2015
DOI: 10.1128/iai.02864-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Clostridium perfringens Beta Toxin Variants with Differing Trypsin Sensitivity and In Vitro Cytotoxicity Activity

Abstract: b By producing toxins, Clostridium perfringens causes devastating diseases of both humans and animals. C. perfringens beta toxin (CPB) is the major virulence determinant for type C infections and is also implicated in type B infections, but little is known about the CPB structure-function relationship. Amino acid sequence comparisons of the CPBs made by 8 randomly selected isolates identified two natural variant toxins with four conserved amino acid changes, including a switch of E to K at position 168 (E168K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…NanI pretreatment increases cytotoxic and binding activity of CPB. While some C. perfringens type C strains produce CPE, all type C strains must (by definition) produce CPB, as must the type B strains that cause enteritis and enterotoxemia in livestock (20,25,26). To evaluate whether NanI enhances the cytotoxic effects of CPB, human umbilical vein endothelial cells (HUVECs) were pretreated with this sialidase, followed by treatment with purified CPB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NanI pretreatment increases cytotoxic and binding activity of CPB. While some C. perfringens type C strains produce CPE, all type C strains must (by definition) produce CPB, as must the type B strains that cause enteritis and enterotoxemia in livestock (20,25,26). To evaluate whether NanI enhances the cytotoxic effects of CPB, human umbilical vein endothelial cells (HUVECs) were pretreated with this sialidase, followed by treatment with purified CPB.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the effects of purified NanI or an rNanI species (described below) on the ability of CPB or CPE to induce cytotoxicity in host cells, an LDH release-based cytotoxicity assay was utilized, as described previously (21). Briefly, HUVECs or Caco-2 cells (sensitive to CPB and CPE, respectively [26,43]) were seeded into 24-well plates and grown as described above until confluent monolayers were achieved. Monolayers were rinsed twice with HBSS (Corning) and treated (as described in the figure legends) for 1 h at 37°C with purified NanI, an enriched rNanI species, or a mock enrichment preparation from an equivalent volume of the empty vector-carrying E. coli culture.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, trypsin inhibitors are required for CPB to retain activity in vivo [ 18 ]. CPB variants have been identified that display different trypsin sensitivity and cytotoxic effects in vitro [ 19 ].…”
Section: Proven or Potential Virulence Factorsmentioning
confidence: 99%
“…Purified CPB is highly sensitive to protease treatment and is thermolabile [23]. As a member of the β-PFT family, CPB shares sequence homology with other toxins, including C. perfringens delta toxin (43% identity) and several S. aureus toxins, including alpha toxin (28% identity) [24].…”
Section: Structure Of Cpbmentioning
confidence: 99%